Transition to a zero-carbon energy system in the Ningxia area: integrated CO2 reduction measures from the multi-level perspective - Qi, Caijuan; Meng, Jinyou; Che, Bin; Kang, Junjie; Zhao, Yingtao; Hua, Zhilei (Frontiers in Energy Research, 2023)
China’s commitments to decarbonization have become the bedrock of national, provincial, and local policymaking across nearly every sector. All its provinces are actively promoting the low-carbon energy transition in pursuit of the carbon neutrality goal. Energy low-carbon transition is complex and comprehensive, which requires an evolution driven from the multi-level perspective, including techno-economic perspective, socio-technical perspective, and policy perspective. In this paper, we constructed five scenarios of low-carbon energy transition in Ningxia Province from the multi-level perspective, namely the business-as-usual scenario (BAU), high electrification scenario (HES), high outward electricity scenario (HOS), low carbon scenario (LCS) and energy-saving scenario (ESS). Based on the LEAP-Ningxia model, we simulated the energy demand from different sectors by 2060 and conducted a quantitative analysis on the primary energy production, secondary energy conversion, final energy consumption, and CO2 emissions. Furthermore, we analyzed the impacts of different CO2 reduction measures from various perspectives to provide scientific support for the zero-carbon energy transition in Ningxia. Under scenarios with CCS and carbon credits, in BAU, HES and HOS, the total CO2 emissions in Ningxia will drop to 17 23 Mt CO2 until 2060. In LCS and ESS, 6 9 Mt CO2 of negative emissions from the energy sector in Ningxia can be achieved until 2060.